A Foresight Study of RFID Passive Tags on Smart Shopping - Nur Aqilah Afiqah Masthoram,; Azizan, Anim Zalina (Research in Management of Technology and Business, 2023)
The existence of useful technology such as RFID passive tags can help facilitate all daily affairs such as not having to queue and wait for a long time to make payments at the counter immediately after shopping. This study aims to identify the challenges, trends, and future issues of the implementation of RFID passive tags from the perspective of the public in Malaysia, which will be obtained from target respondents such as generation Z based in Selangor, considering that Selangor is the most populous state. A descriptive questionnaire based on social, technological, economic, environmental, political, and values (STEEPV) drivers will be utilised to collect data from respondents. STEEPV analysis, scenario building, impact-uncertainty analysis, and descriptive analysis will be used in this study, and data will be analysed using the Statistical Package for Social Science (SPSS) version 22. The data analysed will determine the future images in the implementation of RFID passive tags in smart shopping. This research signifies whether the adoption of RFID passive tags is acceptable among people for future smart shopping.